0.67x+1.33=-0.67

Simple and best practice solution for 0.67x+1.33=-0.67 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.67x+1.33=-0.67 equation:


Simplifying
0.67x + 1.33 = -0.67

Reorder the terms:
1.33 + 0.67x = -0.67

Solving
1.33 + 0.67x = -0.67

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1.33' to each side of the equation.
1.33 + -1.33 + 0.67x = -0.67 + -1.33

Combine like terms: 1.33 + -1.33 = 0.00
0.00 + 0.67x = -0.67 + -1.33
0.67x = -0.67 + -1.33

Combine like terms: -0.67 + -1.33 = -2
0.67x = -2

Divide each side by '0.67'.
x = -2.985074627

Simplifying
x = -2.985074627

See similar equations:

| 5-(x/3)=7 | | 9d-d+4d+6-4d=0 | | 1x-1=5x+3x-8 | | -3z+8+(-12z)=-2 | | 5x+12+x+3x-2=180 | | d+r= | | 2k+5/3+8/3=1/3 | | -3z+8+(-12z)=-12 | | 4x^2-2x+7=0 | | 2x+7=18-20x | | 5g+4(-5+3g)=-1-g | | 2.65=1.8b+3-2.5b | | 2x+5=10x-5 | | .6*x=10 | | 2k+5/3+2/2/3=1/3 | | 2x+4(x-5)=11 | | -0.9b-1.64b=2.794 | | -2.3+0.7x=1+0.6x-1.8x-6.53 | | 5x+5=2x-3 | | -1v+1=-2v+4 | | 15x-4y=6 | | -2.3+0.7x=1+0.6-1.8x-6.53 | | (7+6)2= | | 4x-4+1=21 | | -2.9x-1.5=5.1848+0.3x | | 4(x-4)=40-4x | | y+7=56 | | 36m^5n^2+24m^2n^3-18m^6n= | | 35m^5n^2+24m^2n^3-18m^6n= | | 5x+7=14-13x | | 2y+1=y-1 | | 0.768-b-0.4b=b+1.728 |

Equations solver categories